Factores biológicos y sociodemográficos asociados al dengue en la provincia de Zamora Chinchipe en el período 2015-2020 - Carrión González, Erika Dayanna (2023)
Dengue is a vector disease subject to epidemiological surveillance that affects people of all ages, particularly those who live in tropical areas, constituting a public health problem. For this reason, the objective of this research was to determine the prevalence of dengue and its relationship with biological and sociodemographic factors in the population of Zamora Chinchipe in the period 2015 – 2020. The study had a quantitative, correlational, retrospective and cross-sectional approach. The study population was made up of 335 positive cases of dengue without warning signs (DSSA), the information was compiled from the UNL epidemiological gazette called “Temporal Spatial Distribution of the main diseases in zone 7: Epidemiological Analysis with Geographic Information Systems”. The results obtained regarding the characteristics of the population were that of 335 positive cases, 52,2% belonged to the male sex and 47,8% to the female sex; predominating ages between 20 and 49 years (45,7%), residents mostly in Yanzatza canton (62,7%), coming from de urban area (93,1%) and whose occupation was students (39,7%). The specific prevalence of the desease with respect to the total population of the province was higher in 2019 (178.96 cases per 100.000 inhabitants). On the other hand, it was established that there is a significant association between dengue positivity and factors such as age, occupation, place and origin area of the studied population, these factors must be thoroughly analyzed in future investigations to control the desease. Finally it is concluded that dengue continues to be a problem for the health of the population; therefore, prevention should be prioritized with a focus on the risk factors of the affected population